TINGKAT KEMANDIRIAN PASIEN POST OPERASI LAPARATOMI DENGAN LAMA PERAWATAN DI RUANG BEDAH RSUD MERAXA BANDA ACEH - Teuku Alamsyah; Munita Munita (Poltekkes Kemenkes Aceh, 2023)
Early mobilization is special care given after a medical action in this case is a surgical procedure. This action is done by giving light exercises such as breathing exercises to moving the legs in bed, and inviting the patient to want to walk and move independently to just go to the room bathe. This study aims to determine the relationship between the level of independence of postoperative laparotomy patients and the length of stay at Meuraxa Hospital in Banda Aceh. This type of research was an analytic survey research with a cross sectional approach, namely testing the independent variable (long stay of postoperative patients) with the dependent variable (independence level) with a sample of 10 respondents. Samples were taken from the population using the Accidental Sampling method. This research was carried out from 25 June to 19 July 2019 by distributing questionnaires. Hypothesis testing using the Chi-Square statistical test, data analysis was performed using computer software. The results of this study indicate that there is a relationship between the level of independence of postoperative laparotomy patients and the length of stay, namely: a high level of independence with a length of stay <1 week for 5 people (50%), patients who are not independent with a length of stay >1 week for 4 people (40%) and 1 patient (10%) was not independent for <1 week of treatment. The statistical test results showed that p-value = 0.048 <0.05.